Supermarket Choice and Supermarket Competition in Market Equilibrium - Smith, Howard (Review of Economic Studies, 2004)
Multi-store firms are common in the retailing industry. Theory suggests thatc ross-elasticities between stores of the same firm enhance market power. To evaluate the importance of this effect in the U.K. supermarket industry, we estimate a model of consumer choice and expenditure using three data sources:profit margins for each chain, a survey of consumer choices and a data-set of store characteristics. To permit plausible substitution patterns, the utility model interacts consumer and store characteristics. We measure market powerby calculating the effect of merger and demerger on Nash equilibriumprices. Demerger reduces the prices of the largest firms by between 2 and 3.8% depending on local concentration; mergers between the largest firms lead to price increases up to 7.4%. Copyright The Review of Economic Studies Limited, 2004.